Agribisnis Bandeng Organik: Organic Milkfish Agribusiness - Sabaruddin Sondeng; Ahmad Muhlis Nuryadi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Empowerment of coastal communities is a must because of the many limitations, causing backwardness, especially economically. The specific objective of this program is to realize a pond farming business that has high productivity at low cost and is environmentally friendly so that farming sustainability can be realized, in addition to realizing a farming system with proper management, both production management and institutional and financial management. The method that will be used to achieve this goal is to provide group management and business management training. Business management training is carried out to provide an understanding of the advantages of organic pond cultivation and is also carried out directly in real business. Activities are carried out simultaneously by the group members involved in the planned stages and guided by field staff and the implementing team. The technical stage of its implementation is that the seeds purchased from the hatchery are maintained in a smelting pond for one month. Previously, soil turning, drying, liming, and applying organic fertilizer were carried out. On the other hand, this farmer group can implicitly know and carry out organic farming/fishery activities so that they have supported the government's program on environmentally friendly organic and sustainable farming (Go-Organic).